2018
DOI: 10.1534/g3.118.200672
|View full text |Cite
|
Sign up to set email alerts
|

Budding YeastBFA1Has Multiple Positive Roles in Directing Late Mitotic Events

Abstract: The proper regulation of cell cycle transitions is paramount to the maintenance of cellular genome integrity. In Saccharomyces cerevisiae, the mitotic exit network (MEN) is a Ras-like signaling cascade that effects the transition from M phase to G1 during the cell division cycle in budding yeast. MEN activation is tightly regulated. It occurs during anaphase and is coupled to mitotic spindle position by the spindle position checkpoint (SPoC). Bfa1 is a key component of the SPoC and functions as part of a two-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…4H), we propose that the likely candidate for the inhibitor of Tem1-Cdc15 interaction is Bfa1. In support of this hypothesis, overexpression of Bfa1 without its partner Bub2, arrests cells in anaphase 39,40 , presumably through inhibiting Tem1-Cdc15 interaction.…”
Section: Discussionmentioning
confidence: 80%
“…4H), we propose that the likely candidate for the inhibitor of Tem1-Cdc15 interaction is Bfa1. In support of this hypothesis, overexpression of Bfa1 without its partner Bub2, arrests cells in anaphase 39,40 , presumably through inhibiting Tem1-Cdc15 interaction.…”
Section: Discussionmentioning
confidence: 80%
“…It was previously shown that the overexpression of BFA1 using a galactose-inducible promoter caused inhibition of mitotic exit in a BUB2 -independent manner [ 51 ]. We demonstrated that this defect is due to the role of Bfa1 in Tem1-localization to the SPB and that the defect could be suppressed by concomitant overexpression of TEM1 [ 32 ]. We sought to uncover new modes of MEN regulation by selecting for and characterizing spontaneous suppressors of GAL-BFA1 lethality.…”
Section: Resultsmentioning
confidence: 99%
“…One possible mechanism of action would be early or increased recruitment of Tem1 to the SPBs, as this has been shown to hyperactivate the MEN [ 17 , 29 , 31 ]. The nud1-A308T allele was discovered as a suppressor of lethality in GAL-BFA1 cells, in which Tem1 localization is disrupted ( Figure 1 B; [ 32 ]). Therefore, we looked at Tem1 localization in GAL-BFA1 nud1-A308T cells to determine whether Tem1 recruitment was responsible for the suppression phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the temporal pairing of late mitotic events and cytokinesis, many MEN components are also required for the completion of the cytokinetic process. Amongst them, SPB-bound Tem1 and the Bfa1/Bub2 complex were shown to be crucial for successful cytokinesis ( Whalen et al, 2018 ) and the activity of the SPB-enriched Cdc5 kinase required to complete cytokinesis. In late anaphase, Bfa1 maintains Cdc5 mainly on the cytoplasmic side of the daughter SPB ( Park et al, 2003 ).…”
Section: Centrosomes As Signal Transduction Organizing Centersmentioning
confidence: 99%